Principles of web design - Miller, Brian D. (New York : Allworth Press, 2022)
Author Brian D. Miller is a sought-after expert in developing product and digital branding strategies for emerging startups and Fortune 500 organizations. In Principles of Web Design, he will teach the reader the tricks of the trade and everything one should know about web design through easy, step-by-step guides and with full-color illustrations.
Section 1. Plan -- Section 2. Design -- Section 3. Optimize -- Index.
Previous editions titled Above the fold : understanding the principles of successful Web site design.
Includes index.
Keywords: WEB SITE DEVELOPMENT